The Effects of Gene Duplication Modes on the Evolution of Regulatory Divergence in Wild and Cultivated Soybean - Zhao, Na; Ding, Xiaoyang; Lian, Taotao; Wang, Meng; Tong, Yan; Liang, Di; An, Qi; Sun, Siwen; Jackson, Scott A.; Liu, Bao; Xu, Chunming (Frontiers in Genetics, 2020)
Regulatory changes include divergence in both cis-elements and trans-factors, which play roles in organismal evolution. Whole genome duplications (WGD) followed by diploidization are a recurrent feature in the evolutionary history of angiosperms. Prior studies have shown that duplicated genes have different evolutionary fates due to variable selection constraints and results in genomic compositions with hallmarks of paleopolyploidy. The recent sequential WGDs and post-WGD evolution in the common ancestor of cultivated soybean (Glycine max) and wild soybean (Glycine soja), together with other models of gene duplication, have resulted in a highly duplicated genome. In this study, we investigated the transcriptional changes in G. soja and G. max. We identified a sizable proportion of interspecific differentially expressed genes (DEGs) and found parental expression level dominance of G. max in their F1 hybrids. By classifying genes into different regulatory divergence types, we found the trans-regulatory changes played a predominant role in transcriptional divergence between wild and cultivated soybean. The same gene ontology (GO) and protein family (Pfam) terms were found to be over-represented in DEGs and genes of cis-only between JY47 and GS, suggesting the substantial contribution of cis-regulatory divergences to the evolution of wild and cultivated soybeans. By further dissecting genes into five different duplication modes, we found genes in different duplication modes tend to accumulate different types of regulatory differences. A relatively higher proportion of cis-only regulatory divergences was detected in singleton, dispersed, proximal, and tandem duplicates than WGD duplicates and genome-wide level, which is in line with the prediction of gene balance hypothesis for the differential fates of duplicated genes post-WGD. The numbers of cis-only and trans-only regulated genes were similar for singletons, whereas there were more genes of trans-only than cis-only in the rest duplication types, especially in WGD in which there were two times more trans-only genes than that in cis-only type. Tandem duplicates showed the highest proportion of trans-only genes probably due to some special features of this class. In summary, our results demonstrate that genes in different duplication modes have different fates in transcriptional evolution underpinned by cis- or trans-regulatory divergences in soybean and likely in other paleopolyploid higher organisms.